Feeding the Eternal City: Jewish and Christian Butchers in the Roman Ghetto. By Kenneth Stow. Cambridge, MA; London, UK: Harvard University Press, 2024. ix + 276 pp. $ 45.00 hardback - Zappia, Andrea (Church history, 2025)
Feeding the Eternal City: Jewish and Christian Butchers in the Roman Ghetto. By Kenneth Stow. Cambridge, MA; London, UK: Harvard University Press, 2024. ix + 276 pp. $ 45.00 hardback - Volume 94 Issue 2